Overall Impairment of Quality of Life in Japanese Patients with Hidradenitis Suppurativa: Comparison with National Standard - Koremasa Hayama; Hideki Fujita; Takashi Hashimoto; Tadashi Terui (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)